The Pakistan Army 1966-71 - Shaukat Riza, Major General (Rawalpindi Services Book Club, 1990)
This books covers the army activities between the years of 1966 to 1971
Include Bibliography and Index
Keywords: Pakistan. Army -- Pakistan, Military